2017
DOI: 10.1038/ni.3788
|View full text |Cite
|
Sign up to set email alerts
|

Germinal-center development of memory B cells driven by IL-9 from follicular helper T cells

Abstract: Germinal centers (GCs) support high-affinity, long-lived humoral immunity. How memory B cells develop in GCs is not clear. Through the use of a cell-cycle-reporting system, we identified GC-derived memory precursor cells (GC-MP cells) that had quit cycling and reached G0 phase while in the GC, exhibited memory-associated phenotypes with signs of affinity maturation and localized toward the GC border. After being transferred into adoptive hosts, GC-MP cells reconstituted a secondary response like genuine memory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
145
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(154 citation statements)
references
References 55 publications
8
145
1
Order By: Relevance
“…The output from GCs switches markedly from generation of memory B cells at the early stage to genera- 63 The kinetics of IL-9 + Tfh cells during the GC response are unclear, but they may be extinguished in late GCs. The output from GCs switches markedly from generation of memory B cells at the early stage to genera- 63 The kinetics of IL-9 + Tfh cells during the GC response are unclear, but they may be extinguished in late GCs.…”
Section: Temp or Al Reg Ul Ati On Of G C Outputmentioning
confidence: 99%
“…The output from GCs switches markedly from generation of memory B cells at the early stage to genera- 63 The kinetics of IL-9 + Tfh cells during the GC response are unclear, but they may be extinguished in late GCs. The output from GCs switches markedly from generation of memory B cells at the early stage to genera- 63 The kinetics of IL-9 + Tfh cells during the GC response are unclear, but they may be extinguished in late GCs.…”
Section: Temp or Al Reg Ul Ati On Of G C Outputmentioning
confidence: 99%
“…7,10,11 It has been shown that IL-9 can enhance B-cell and antibody responses, [12][13][14][15] including by a T follicular helper (Tfh) cell subset that produces IL-9 and promotes the germinal center response for memory B-cell development. 16,17 An IL-9 producing CD8+ T cell subset has also been reported that may have tumoricidal activity. 18 In addition to T cells, IL-9 is produced by other cell types including type II innate lymphocyte cells (ILC2) and mast cells that all cross talk with Th9 cells in processes that still remain poorly resolved, yet likely have substantial implications.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25] IL-9R is expressed on various T-cell subsets including effector T cells, Th2, and Th17 cells, but not on naïve T cells. [25][26][27][28] IL-9R is also expressed by B cells, particularly GC B cells. [15][16][17] IL-9R is expressed on mast cells, polymorphonuclear cells in the lungs, non-hematopoietic cells, including airway epithelial cells which increase mucus production in response to IL-9, and by smooth muscle cells which produce IL-8, IL-13, and eotaxin in response to IL-9, 29-31 underlining its role in regulating mucosal immunity.…”
Section: Introductionmentioning
confidence: 99%
“…By the time activated CD4 + T cells become fully competent effector cells, they are generally thought of as functionally polarized in one or another lineage, although some clone members may maintain a level of plasticity, remain responsive to distinct differentiation cues, and therefore are able to trans-differentiate in environment conducive to choices of other lineages. In addition to IL-21, T FH cells have been found in various models of infection and immunization to produce IFNγ, 6 IL-4, 7-9 IL-17, 10 IL-9, 11 and IL-10, 12 all of which can modulate certain but not all aspects of GC biology. 4 Th1, Th2, and Th17 cells all have signature cytokines that are responsible for their respective lineage-defining functions, and expression of those cytokines are transcriptionally and epigenetically controlled by their respective lineage-specifying master transcription regulators.…”
Section: Introductionmentioning
confidence: 99%
“…4 Th1, Th2, and Th17 cells all have signature cytokines that are responsible for their respective lineage-defining functions, and expression of those cytokines are transcriptionally and epigenetically controlled by their respective lineage-specifying master transcription regulators. 11 Albeit not formally excluded, the possibility that any single T FH cells could produce all of these cytokines at the same time is extremely small. In addition to IL-21, T FH cells have been found in various models of infection and immunization to produce IFNγ, 6 IL-4, 7-9 IL-17, 10 IL-9, 11 and IL-10, 12 all of which can modulate certain but not all aspects of GC biology.…”
Section: Introductionmentioning
confidence: 99%